EFFECT OF COPPER SULPHATE (CUSO4) ON BEHAVIOUR AND ON LIVER OF CLARIAS BATRACHUS (LINN. 1758) - BEENA JOSHI BHATT,; SHAGUFTA MAQSOOD, (International Journal of Pharma and Bio Sciences, 2015)
The heavy metal toxicants accumulate in the fish through the general body surface which affects severely their life support system. Once these toxic substance enter into the fish body, they damage and weaken the mechanism concerned leading to physiological, pathological and biochemical disorders. The present study proved that the heavy metal salts, i.e. copper sulphate impacts on behavioral responses in fresh water breathing fish Clarias batrachus (Linn.). Histological studies have revealed that the liver sections from control fishes showed normal histoarchitecture, The liver is characterized by polygonal shaped hepatocytes with granular cytoplasm and centrally placed round nuclei. Hepatocytes were arranged in well organized hepatic cords and separated by narrow blood sinusoids. Liver of fishes exposed to 1.5 ppm, 2.0 ppm and 3.0 ppm copper sulphate for 30 days resulted in the loosening of hepatic tissue, vacuolization, enucleated and distended hepatocytes and the centrally situated nuclei have shifted to the periphery of the cells.